Prediction of the performance of synthetic sheep strains utilizing Finnsheep and native sheep breeds in Egypt - Mansour, H.; Aboul-Naga, A. M. (Agricultural and Food Science, 1988)
This investigation was carried out to estimate individual and maternal heterotic components for ewe productivity traits to enable predicting the performance of synthetics including local (Rahmani (R) and Ossimi (O)) and Finn (F) inheritance. Reproduction performance traits studied were number of ewes conceived (ECJ), number of lambs born (LBJ), number of lambs at four months of age (L4J), kilograms born (KBJ) and kilograms at four months of age (K4J), all being per ewe joined, and number of lambs born (LBL), number of lambs at four months of age (L4L), kilograms born (KBL) and kilograms at four months of age (K4L), all being per ewe lambed. Results indicate an expected increase of 0.32, 0.19, 0.50 and 0.27 in LBJ, L4J, LBL and L4L for F.R and 0.32, 0.23, 0.59 and 0.40 in the same traits for F.O after two generations of interse mating, respectively. For FR.R and FO.O the improvements were(0.18, 0.18), (0.13, 0.15), (0.22, 0.28) and (0.15, 0.22) in LBJ, L4J, LBL and L4L, resp. It can be concluded that introducing the F to the local subtropical sheep in Egypt would substantially improve their reproductive performance whether for implementation at the small farmer level (quarter F) or at higher intensification level (half F).